2015
DOI: 10.1088/0004-637x/799/2/144
|View full text |Cite
|
Sign up to set email alerts
|

THE M31 NEAR-INFRARED PERIOD-LUMINOSITY RELATION AND ITS NON-LINEARITY FOR δ Cep VARIABLES WITH 0.5 ⩽ log (P) ⩽ 1.7

Abstract: We present the largest M31 near-infrared (F110W (close to J band), F160W (H band)) Cepheid sample so far. The sample consists of 371 Cepheids with photometry obtained from the HST PHAT program. The sample of 319 fundamental mode Cepheids, 16 first overtone Cepheids and 36 type II Cepheids, was identified using the median absolute deviation (MAD) outlier rejection method we develop here. This method does not rely on priors and allows us to obtain this clean Cepheid sample without rejecting a large fraction of C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
49
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(59 citation statements)
references
References 33 publications
7
49
3
Order By: Relevance
“…In comparison with the Cepheid P-L relation, the TRGB was used to measure distance to a much larger number of galaxies, including galaxies that lack young standard candles like classical Cepheids. Cepheid distance measurements are also affected by numerous systematic errors including reddening, a possible metallicity dependence, or a nonlinearity of the P-L relation (Kodric et al 2015). Therefore the TRGB method is an important tool that can complement and perhaps improve the determination of the Hubble parameter.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with the Cepheid P-L relation, the TRGB was used to measure distance to a much larger number of galaxies, including galaxies that lack young standard candles like classical Cepheids. Cepheid distance measurements are also affected by numerous systematic errors including reddening, a possible metallicity dependence, or a nonlinearity of the P-L relation (Kodric et al 2015). Therefore the TRGB method is an important tool that can complement and perhaps improve the determination of the Hubble parameter.…”
Section: Introductionmentioning
confidence: 99%
“…We All samples show no evidence of a broken slope. Previously in Kodric et al (2015) we found a significant broken slope. We find that the broken slope is caused by a subsample of Cepheids that have a different color from the other Cepheids and have a high extinction but are otherwise the same.…”
Section: Resultsmentioning
confidence: 64%
“…Riess et al (2012). Also shown are the slopes from Kodric et al (2013), Kodric et al (2015) and Kodric et al (2018a). The fits to the FM Cepheids shown in table 2, table 5 and table 8 are also shown.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The two most notable uses are the massive surveys of M33 (Hartman et al 2006) and M31 (Kodric et al 2013(Kodric et al , 2015 using the MMT and the Pan-STARRS telescopes, respectively. Unfortunately, despite concerted efforts over the past decade (Ribas et al 2005;Bonanos et al 2006;Vilardell et al 2010) neither galaxy has a distance estimate as robust as that for the LMC by Pietrzyński et al (2013)…”
Section: Fiducial Cepheid P-l Relations In Sdss Filtersmentioning
confidence: 99%